1975
DOI: 10.1136/bmj.3.5976.128
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of acute systolic hypertension after myocardial infarction.

Abstract: SummaryThe clinical behaviour and mean peak serum aspartate aminotransferase (SGOT) values of 106 patients admitted to a coronary care unit with acute myocardial infarction who displayed acute systolic hypertension were studied. Another 106 normotensive patients with acute myocardial infarction acted as controls. Neither group had established hypertension. The mortality rate, incidence of cardiac failure, major arrhythmias, and mean peak SGOT were significantly greater in the hypertensive group, within which t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Furthermore, the timing of the intervention, a minimum of 7 h after hospital admission, would render infarction reduction less probable (Maroko et al, 1978). No (Fox et al, 1975;Rosenbaum & Levine, 1941).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the timing of the intervention, a minimum of 7 h after hospital admission, would render infarction reduction less probable (Maroko et al, 1978). No (Fox et al, 1975;Rosenbaum & Levine, 1941).…”
Section: Discussionmentioning
confidence: 99%
“…MYOCARDIAL infarction complicated by systemic hypertension has been associated with a higher incidence of left ventricular failure, major arrhythmia and hospital death (Fox et al, 1975;Rosenbaum & Levine, 1941). The improved coronary perfusion resulting from raised systemic BP in this situation probably does not compensate for the increased myocardial oxygen consumption occasioned by elevated afterload, with consequent impairment of myocardial function.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Criteria for inclusion were: (1) acute (less than 48 hours) infarction (that is severe chest pain, appearance of new Q waves and/or abnormal levels of MB Accepted for publication 3 February 1983 creatinine kinase); (2) systemic hypertension (systolic value greater than 150 mmHg) persisting over six hours in spite of adequate sedation and control of chest pain; (3) normal sinus rhythm; and (4) cardiac index greater than 2*4 1/min per M2.…”
Section: Methodsmentioning
confidence: 99%
“…35 Acute elevation of blood pressure in the setting of acute myocardial infarction may be transient and not harmful,36 but others have observed that the mortality rate and the incidence of cardiac failure were significantly greater in patients with severe systolic hypertension and acute myocardial infarction. 37 Reduction of systemic arterial pressure early in the course of acute myocardial infarction has been shown to protect the myocardium as reflected by reduced release of creatine phosphokinase (CPK) enzyme activity. 35 Thus, cautious treatment of hypertension in patients with acute myocardial infarction is likely to be beneficial.…”
Section: Severementioning
confidence: 99%